Nilai Nilai Pendidikan Islam Dalam Tradisi Al-Berzanji Pada Masyarakat Desa Wonosari Kecamatan Bengkalis Kabupaten Bengkalis - Sugiarto, wira (Darul Ilmi: Jurnal Ilmu Kependidikan dan Keislaman, 2022)
The cultural value system is the core of culture, as its core it will influence and organize the elements that are on the surface structure of human life which includes behavior as a unitary symptom and objects as a material unit. The cultural value system consists of the conceptions that live in the minds of most citizens, regarding things that they should consider very valuable in life. Therefore, a system of cultural values usually functions as the highest guideline for human behavior. more obvious symptoms such as behavior and material objects as a result of pouring out value concepts through patterned actions. The cultural values contained in these customs and traditions are very important for people who still adhere to customs and traditions in social life in Wonosari village, in the walimahan tasmiyah procession, commemoration of the Prophet's birthday and weddings, the implementation of the event still uses customs and traditions. which has become the culture of the local community.